2011
DOI: 10.1007/978-1-61779-421-6_15
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Methods in Human Biomonitoring: Principles and Uses

Abstract: Cellular phenotypes can be applied as biomarkers to differentiate normal from abnormal biological -conditions. Several cytogenetic methods have been developed and allow the accurate detection of such phenotypic changes.Based on their mechanisms of formation, cellular phenotypes may be used either as biomarkers of exposure or as biomarkers of effect. Therefore, it is important that cytogenetic methods implemented in human biomonitoring should be based on a good knowledge of these mechanisms.In this chapter, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 114 publications
0
19
0
1
Order By: Relevance
“…However, it is agreed that SCEs are initiated by the collapse of a replication fork when it encounters a break in one parental strand. Repair of the stalled fork is mediated by a homologous recombination pathway that might result in SCEs [41]. In addition, previous studies have suggested a lack of association between SCEs and cancer prediction [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is agreed that SCEs are initiated by the collapse of a replication fork when it encounters a break in one parental strand. Repair of the stalled fork is mediated by a homologous recombination pathway that might result in SCEs [41]. In addition, previous studies have suggested a lack of association between SCEs and cancer prediction [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that neither the clinical significance nor the mechanisms that lead to the formation of SCEs are understood [41]. However, it is agreed that SCEs are initiated by the collapse of a replication fork when it encounters a break in one parental strand.…”
Section: Discussionmentioning
confidence: 99%
“…19) The biomarker has been widely used to detect chromosome instability potential for a variety of xenobiotics in both in vitro and in vivo experimental models, as well as to evaluate the genotoxic effect caused by exposure to industrial, environmental, cosmetic or pharmaceutical agents, among others. 20,21) In regard to carcinogenesis, the induction of SCE has been considered of lower relevance, however, it is pertinent to mention that in diseases such as Bloom syndrome and Fanconi anemia spontaneous or induced SCE are usually found in excess, and that both conditions are prone to develop cancer; moreover, in other types of cancer SCE has been a useful biomarker, for example, in familial breast cancer patients. 22) In the case of antidepressants the assay has also been successfully applied.…”
Section: Discussionmentioning
confidence: 99%
“…These disturbances lead to cell death, apoptosis and malignant transformation. CA reflect an individual's susceptibility to a complex of endogenous and exogenous factors and can be markers of genotoxic risk (Mateuca et al 2012;Vodenkova et al 2015). Significant research indicates that cytogenetic indicators are useful biomarkers for genotoxic and carcinogenic responses (including the influence of radiation) in occupational and domestic conditions (Norppa 2004).…”
Section: Introductionmentioning
confidence: 99%